Enzyme-assisted ReMALDI-MS assay for quantification of cholesterol in food. (30th July 2022) - Li, Bin; Gao, Wenjing; Ling, Ling; Yu, Shaoning
Graphical abstract: Highlights: A simple and quantitative MALDI-MS-based assay for cholesterol is established. The reactive matrix improved the sensitivity and specificity. The method was successfully used for quantification of cholesterol in food. Abstract: Cholesterol is a vital building block for animal cell membranes and participates in the synthesis of various hormones. Accurate quantitation of cholesterol in food is crucial for healthy diets. Here, we describe an enzyme-assisted reactive matrix-assisted laser desorption/ionization mass spectrometry ( Re MALDI-MS) assay for the quantification of cholesterol in food. First, cholesterol was converted to 4-cholesten-3-one using the cholesterol oxidase, and then reacted with a reactive matrix, 4-hydrazinoquinazoline (4-HQ), to form a hydrazone bond. Utilizing 4-HQ significantly improved the ionization efficiency of cholesterol, which possesses poor ionization efficiency in MALDI-MS, and no additional tedious derivatization/purification steps were needed. Thus, the proposed assay was successfully used for the quantification of cholesterol in bovine milk and cream. The standard recovery tests show a recovery range of 95.3–103.0% with a relative standard deviation of 0.3–3.1%. Therefore, the proposed enzyme-assisted Re MALDI-MS assay has great potential for quantification of cholesterol in other foods.